Community Empowerment Through the Processing of Household Organic Waste into Fermented Animal Feed in Dusun Patra, Sangkima Village: Pemberdayaan Masyarakat Melalui Pengolahan Limbah Organik Rumah Tangga Menjadi Pakan Ternak Fermentasi di Dusun Patra, Desa Sangkima - Alifia Nur As Syifa Hamka; Muhammad Rizqy Septyandy; Muhamad Fadly Arif; Nurul Vita Azizah; Hajrah; Trisnaweldy Manurung; Vera Indriani; Silva Jen Retno; Bimasakti Cahyo Utomo; Maulana Al Amin (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2026)
This community engagement program aimed to empower the residents of Patra Sub-Village, Sangkima Village, by converting household organic waste into fermented animal feed. The activity addressed the dual challenges of the high cost of commercial feed and the accumulation of unmanaged organic household waste. The program utilized a demonstrative method, including socialization sessions and practical training on the fermentation of organic waste using Effective Microorganism 4 (EM4) technology. Evaluation through pre-tests and questionnaires revealed a significant increase in participants’ knowledge and awareness, with most attendees considering the materials easy to understand and apply. The initiative successfully reduced participants' feed expenses by up to 30% and fostered a sustainable, environmentally friendly waste management culture. Ongoing assistance and advanced training in feed packaging are recommended to ensure the continuity and commercial potential of this innovation in the local community.